Is Full-Fledged Sharia General Insurance More Efficient Compared to Sharia Business Units (UUS)? An Efficiency Evaluation Study Towards the Mandatory Spin-Off Period in Indonesia - Marsella, Marsella; Nurzaman, Mohamad Soleh; Anwar, Saiful (The International Journal of Financial Systems, 2025)
This study explores the comparative efficiency of Islamic general insurance providers in Indonesia, focusing on full-fledged companies versus Islamic business units (UUS), particularly in light of the mandatory spin-off policy. Covering the period from 2017 to 2022, we adopt a two-stage analytical approach. First, we apply a non-parametric method — Data Envelopment Analysis (DEA) — to measure efficiency levels, using assets and business expenses as input variables, and net profit along with operating income as output variables. In the second stage, we employ Tobit regression to investigate the key drivers of efficiency, using the DEA scores as the dependent variable and Return on Assets (ROA), Return on Equity (ROE), Current Ratio, and Risk-Based Capital (RBC) as explanatory factors. Our findings reveal that Islamic business units consistently outperform full-fledged Islamic insurers in achieving higher efficiency. Furthermore, ROA emerges as a significant positive determinant of efficiency, while the Current Ratio shows a significant negative impact. In contrast, ROE and RBC do not exhibit significant influence on efficiency levels. These insights contribute to the discourse on the operational dynamics of Islamic insurance, offering practical implications for regulators and industry stakeholders navigating the evolving Sharia insurance landscape in Indonesia.